2017
DOI: 10.1038/s41562-017-0215-1
|View full text |Cite
|
Sign up to set email alerts
|

The idiosyncratic nature of confidence

Abstract: Confidence is the ‘feeling of knowing’ that accompanies decision making. Bayesian theory proposes that confidence is a function solely of the perceived probability of being correct. Empirical research has suggested, however, that different individuals may perform different computations to estimate confidence from uncertain evidence. To test this hypothesis, we collected confidence reports in a task where subjects made categorical decisions about the mean of a sequence. We found that for most individuals, confi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
113
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 46 publications
16
113
1
Order By: Relevance
“…the orientation of the stimulus (Rausch et al, 2015;Rausch & Zehetleitner, 2016). However, previous studies indicated (Navajas et al, 2017;Rausch et al, 2018) and Exp. 2 corroborated the view that sensory evidence about identity-irrelevant features of the stimulus are involved in the calculation of decisional confidence, too.…”
Section: Discussionmentioning
confidence: 87%
“…the orientation of the stimulus (Rausch et al, 2015;Rausch & Zehetleitner, 2016). However, previous studies indicated (Navajas et al, 2017;Rausch et al, 2018) and Exp. 2 corroborated the view that sensory evidence about identity-irrelevant features of the stimulus are involved in the calculation of decisional confidence, too.…”
Section: Discussionmentioning
confidence: 87%
“…In our noreport conditions, instead, responses were completely absent and may have shifted participant's global strategies for the computation of confidence. In other words, we contest that while first-order reaction time information is, under some experimental settings used by participants to generate a confidence judgement, when motor information is not available at all, it may be replaced by other, equally precise sources of information, closer to the strength of evidence (such as the probability of being correct (Sanders et al, 2016), the internal signal noise (Navajas et al, 2017) and the evidence in favour of the chosen response alternative (Peters et al, 2017). This admittedly speculative account is compatible with our capacity to form confidence estimates about decisions that are not directly linked to a transient motor action, for instance when controlling a brain machine interface (Schurger, Gale, Gozel, & Blanke, 2017) or when making global confidence judgments in ecological contexts (Rouault, Dayan, & Fleming, 2019).…”
Section: Differences With the Existing Literaturementioning
confidence: 99%
“…on the posterior probability of being correct. Although one study found that confidence ratings are consistent with computations based on the posterior probability (Sanders et al 2016; but see Adler & Ma 2018b), others showed that either some (Aitchison et al 2015;Navajas et al 2017) or most (Adler & Ma 2018a;Denison et al 2018) observers are described better by heuristic models in which confidence depends on uncertainty but not on the actual posterior probability of being correct.…”
Section: Confidence Does Not Simply Reflect the Posterior Probabilitymentioning
confidence: 92%